Laparoscopic versus open pancreatectomy for pancreatic ductal adenocarcinoma: A systematic review and meta-analysis. (May 2018) - Chen, Ke; Pan, Yu; Zhang, Bin; Maher, Hendi; Cai, Xiu-jun
Abstract: Background: Laparoscopic pancreatic surgery (LPS) has been widely used in the treatment of benign and low-grade pancreatic diseases. It is necessary to expand the current knowledge on the feasibility and safety of LPS for pancreatic ductal adenocarcinoma (PDAC) by systematic reviewing the published studies and analyzing them by meta-analysis. Methods: Original articles compared LPS with open pancreatic surgery (OPS) for PDAC, published from January 1994 to August 2017 were searched in medical databases. Postoperative pancreatic fistula (POPF), morbidity, mortality, operation time, blood loss, transfusion, hospital stay, retrieved lymph nodes (RLNs), and survival outcomes were compared. Results: Fourteen studies with a total of 13174 patients (1705 in LPS and 11469 in OPS) were included for the meta-analysis. LPS showed less morbidity (RR = 0.78, 95%CI: 0.66–0.92, P < .01), blood loss (WMD = −298.05 ml, 95% CI, −482.98∼-113.12 ml; P < .01), shorter hospital stay (WMD = −2.86, 95%CI, −3.85∼-1.87; P < .01), more RLNs (WMD = 1.47, 95%CI: 0.15–2.78; P = .03) and comparable POPF (RR = 1.12, 95%CI: 0.82–1.53, P = .50), operation time (WMD = 22.23 min; 95%CI: −19.56–64.01, P = .30), and 5-year overall survival (HR = 0.92, 95%CI: 0.80–1.06; P = .23) compared to OPS. Conclusion: LPS can be performed safely in carefully selected patients with PADC and would improve the surgical outcomes. Considering the limitation of study design, the conclusions should be interpret cautiously and warrant to be confirmed by randomized controlled studies. Highlights: Laparoscopic pancreatic surgery can be performed safely for pancreatic duct adenocarcinoma. Laparoscopic pancreatic surgery has advantages in less postoperative morbidity, less blood loss, and shorter hospital stay. Laparoscopic pancreatic surgery has similar oncological outcomes as compared with open countpart.